2006
DOI: 10.1177/0962280206070621
|View full text |Cite
|
Sign up to set email alerts
|

Efficient interval estimation for age-adjusted cancer rates

Abstract: The age-adjusted cancer rates are defined as the weighted average of the age-specific cancer rates, where the weights are positive, known, and normalized so that their sum is 1. Fay and Feuer developed a confidence interval for a single age-adjusted rate based on the gamma approximation. Fay used the gamma approximations to construct an F interval for the ratio of two age-adjusted rates. Modifications of the gamma and F intervals are proposed and a simulation study is carried out to show that these modified ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
352
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(356 citation statements)
references
References 10 publications
4
352
0
Order By: Relevance
“…The differences in rates between men and women and among whites, African Americans, and individuals of all other racial groups were examined by calculating rate ratios (RRs) and the corresponding 95% CIs, as described by Tiwari et al 17 Changes in incidence over time were expressed as the annual percentage change (APC) and were examined further using the Joinpoint Regression Program (Control and Population Sciences, National Cancer Institute, Bethesda, Md). The APC was calculated by fitting a least-squares regression line to the natural logarithm of the rates using the calendar year as a regressor variable.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in rates between men and women and among whites, African Americans, and individuals of all other racial groups were examined by calculating rate ratios (RRs) and the corresponding 95% CIs, as described by Tiwari et al 17 Changes in incidence over time were expressed as the annual percentage change (APC) and were examined further using the Joinpoint Regression Program (Control and Population Sciences, National Cancer Institute, Bethesda, Md). The APC was calculated by fitting a least-squares regression line to the natural logarithm of the rates using the calendar year as a regressor variable.…”
Section: Methodsmentioning
confidence: 99%
“…We did not examine in situ cervical tumors, which have not been reportable to NPCR and SEER since 1996. All analyses were limited to cervical carcinomas by using specific histologies defined in Table 1 18 Rates were calculated in SEER*Stat, standardized to the 2000 US Standard Population, and expressed per 100,000 women; limits of confidence intervals were 95% and were based on the Gamma method using the modification described by Tiwari et al 19 Age-adjusted rates of invasive cervical carcinoma incidence are reported for race, Hispanic ethnicity, histology, stage, and US census region. Racial groups examined include white, black, and Asian-Pacific Islander (API); 'all races' also includes other and unknown categories.…”
Section: Methodsmentioning
confidence: 99%
“…Rates and 95% modified g confidence intervals (CIs) were generated by using SEER*Stat software version 6.3.6. 24,25 Percentage distributions also were age-adjusted. Rate ratios with 95% CIs were provided for regional comparisons of incidence rates between AI/AN and NHW populations ( Table 1).…”
Section: Population Estimatesmentioning
confidence: 99%